Annual Plan and Budget-Link 1970-71 Government of Assam - Planning Commission (Planning Commission, 1970)
Schemewise analysis in terms of Plan & Budget Head of Development Minor Irrigation Scheme-wise analysis in terms of plan and the Budget Scheme-wise analysis in terms of plan and the Budget Head of Department Ayacut Development Programme Scheme-wise analysis in terms of plan and the Budget Head of Dev Animal Husbandry Centrally Sponsored Schemes Head of Department Animal Husbandry Animal Plan for 1970-71 Schemewise analysis in terms of Plan Budget Head of Development Dairying & Milk Supply.
Government of Assam, Planning and Development Department